Analisis Location Quotient dalam Penentuan Sektor Basis dan Non Basis di Kabupaten Gorontalo - Kalzum R. Jumiyanti (Gorontalo Development Review, 2018)
Identifying basic sectors and sub-sectors is one of stages to plan strategic area expansion for the centre of economy growth. Therefore, Location Quotient Analysis is needed to understand how far the level of specialization of economy sectors in particular area in utilizing its basis sectors or leading sectors. Basic sectors can be determined by using Location Quotient (LQ) method. Variables used to calculate basis economy are from local GDP of an activity focused on activities in the local economy structures. Gross Domestic Product (GDP) is an  important indicator to understand economy condition particularly in Gorontalo  Regency in particular period, either based on current prices or constant price. Data collection process done by using secondary data survey based on documents from Statistics of Gorontalo Regency and Statistics of Gorontalo Province. From 2012 up to 2016, processing industry sectors and  service sectors have been stable basis in terms of improving LQ value and its GDP in an analysis period. This can be possible that those two sectors have contributed on the improvement of GDP of Gorontalo Regency including all other sectora that also become basis  such as Mining and Excavation sector, agriculture  sector and others.